(untitled) (Journal of the College of Basic Education, 2022)
News casts rely on all radio and television stations on the structural templates promise the most important news , Report , interview , Talk . . etc . Tv report serves as ample space with in the structure of a news bulletin to its importance in better circumstances Arab security , political and mathematically and technically . That the recipient of the Iraq whatever sex need to know the full details of any news broadcast through the media . and competent channel Aln cost one of their correspondents in digging a details of this news through the television industry professional to the report , which constitutes one – third of the news letter . The researcher of this study was divided in to several chapters , entitled methodological frame work Game to search . GS has included research problem which can be summarized to how the study of the function of the television report in the news bulletin through the study of the public . This included research on the importance and goals of the disclosure of the report function . The second chapter included a theoretical frame work has been divided researcher to two sections of this chapter are the concept of the report and its importance to our news letter . The third chapter deals with measures such as research methodology , Areas of research , Find community , search tool and building from analysis . The fourth quarter has included analysis according to the form of analysis and derive the desired results of the analysis , and perhaps most notably for Al- Arabiya a first place by (4.26%) and that all the respondents who watch the Arab satellite news watching the news reports , and by (100%) . As well as the implications of political topped the contents favored . Respondents in the reports they see and by (68.42%) . has included on the recommendations and a list of sources and a summary of the study in English .